Validity Test of Digital Science Teaching Materials Based on Case Method Learning Integrated with P5P2RA - Efrahutatera; Jayanti Syahfitri; Merri Sri Hartati (Postgraduate, University of Mataram, 2025)
This study aims to develop digital science learning media based on case method learning integrated with P5P2RA. The main data of this study are (a) knowing the facilities owned by the school based on the results of interviews with the principal, (b) learning media used by teachers during learning based on interviews with class teachers, (c) Practicality when used by students based on the results of student observations. This study uses the research and development (R&D) method. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results of the study indicate that (a) the facilities owned by the school can be used well, and (b) the media developed is feasible for use in the classroom, this can be seen from the results of media expert validation of 91% and material expert validation of 90% with a very feasible category (c) digital science learning media based on case method learning integrated with P5P2RA is stated to be practical, this can be seen from the results of the Practicality Test of 92.6% with a very practical category.